2010
DOI: 10.1002/ajp.20800
|View full text |Cite
|
Sign up to set email alerts
|

Prey capture efficiency in brown capuchin monkeys (Cebus apella) is influenced by sex and corpus callosum morphology

Abstract: The diet of capuchin monkeys consists largely of fruits, but these monkeys commonly prey upon insects and other invertebrates as well as vertebrates such as lizards, birds, and fish. Capturing small fast-moving prey requires the ability to process complex visuospatial information such as motion detection, shape, and pursuit. Here we report the results of an experimental investigation into whether capuchins display sex differences in prey capture efficiency, and whether these differences are associated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
1
15
1
Order By: Relevance
“…Contrary to our findings of left-hand preference for four of five female capuchins in capturing crickets, a previous study in which tufted capuchin monkeys captured freely swimming small fish reported a significant left-hand preference for male capuchins (N ¼ 3) whereas females (N ¼ 4) showed no significant hand preference (Hellner-Burris et al, 2010). Sex may not be a parameter influencing the hand preference in capuchins.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to our findings of left-hand preference for four of five female capuchins in capturing crickets, a previous study in which tufted capuchin monkeys captured freely swimming small fish reported a significant left-hand preference for male capuchins (N ¼ 3) whereas females (N ¼ 4) showed no significant hand preference (Hellner-Burris et al, 2010). Sex may not be a parameter influencing the hand preference in capuchins.…”
Section: Discussioncontrasting
confidence: 99%
“…This is suggested by the finding that mouse lemurs, Microcebus murinus, grab stationary food with the mouth but moving prey with the hands (Toussaint et al, 2013). In primates, catching fast-moving prey involves the integration of visuospatial information about the trajectory and speed of the prey with aimed rapid movement of the forelimb (Hellner-Burris et al, 2010). The right hemisphere is known to be used for spatial processing in many species (rats: Cowell, Waters, & Denenberg, 1997; chickens, Gallus gallus domesticus: Tommasi & Vallortigara, 2004;humans: Wendt & Risberg, 1994;De Renzi, 1982;other species: Vallortigara & Rogers, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In placental mammals the size of the corpus callosum was found to be inversely linked with asymmetry expression [96-98]. Furthermore, the sexual dimorphism in the corpus callosum size seems to be associated with differences in motor laterality in males and females [99-102]. The alternative way of interhemispheric connection may result in a fundamentally distinct mechanism of sex effect on limb preferences in marsupials compared to placentals.…”
Section: Discussionmentioning
confidence: 99%
“…An example of how growth in the tracts of the CC might be associated with the development of skilled foraging concerns the complex foraging skill of prey capture. The increase in posterior region of the CC, the splenium, which connects information between parietal and temporal lobes and is associated with visuospatial skills, may be linked to skills such as prey capture (Hellner-Burris et al 2010), Phillips, unpublished results). Ongoing longitudinal research in our laboratory is exploring these questions, and has the potential to provide a more accurate means of tracking the development of the CC in capuchins and integrating brain development with development of cognitive and motor abilities.…”
Section: Discussionmentioning
confidence: 99%